Locating Knowledge in Góngora and Borges. Issue 7 (13th September 2016) - Kerr, Lindsay; Richardson, Bill
Abstract: This paper explores the role of the imagination in our understanding of the nature of knowledge, through the synchronic interaction of the works of Luis de Góngora and Jorge Luis Borges, respectively. We discuss the supposed 'world of écriture ' and 'blinding' metaphors of the former, and the spatial shift between self and universe that metaphor entails, in the latter. We also highlight some of the ways in which the two bodies of work relate to each other, and speak to us about how imagination relates to understanding, particularly through the short story 'El Aleph' and Borges' later reappraisal of Gongorine methods. The lesson that Góngora and Borges teach us about such explanations is twofold: firstly, that any explanation is only every partial, and secondly, that explanations can only ever be indirect and are always mediated by the imagination. Ultimately, the irony is that, for these authors, a large element of the 'truth' that we achieve is an understanding about the limited nature of understanding itself.